Antioxidative Effect of Coconut (Cocos nucifera L.) Water Extract on TBARS Value in Liver of Rats Fed Fish Oil Diet - Umar Santoso; Kazuhiro Kubo; Toru Ota; Tadahiro Tadakoro; Akio Maekawa (Indonesian Food and Nutrition Progress, 1996)
Ethanolic extract of the coconut water showed antioxidant activity in the in vitro assay using an emulsified-aqueous system containing linoleic acid and /3-carotene. To evaluate the possible antioxidative effect in vivo, a study with rats fed fish oil diet, was performed. Oral administration of the coconut water extract (CWE, 340mg/mL) did not influence food intake, daily body weight gain nor average liver weight of rats. It was investigated that the increase of liver TBARS value of rats fed fish oil diet was significantly (P < 0.01) suppressed by oral administration 0.8 ml of the coconut water extract (CWE 340 mg/ml)/rat twice per day during 14 days of experimental period. Oral administration of coconut water extract also tended to suppress the decreasing effect of fish oil diet on liver ascorbic acid. Liver total glutathione of rats fish oil diet was significantly lower than that of rats fed AIN-93G standard diet, but oral administration of the coconut water did not significantly change the liver glutathione. SOD activity in liver homogenate of rats fed fish oil diet and orally administrated by coconut water extract was significantly higher than that of those orallyadministrated by water. The result showed that the antioxidative properties of the coconut water extract have been demonstrated by in vivo assay using rats fed fish oil diet.